2021
DOI: 10.1111/1467-8551.12585
|View full text |Cite
|
Sign up to set email alerts
|

Equity Crowdfunding: The Influence of Perceived Innovativeness on Campaign Success

Abstract: This paper examines the impact of perceived innovativeness on the success of equity crowdfunding campaigns. Building on the investor perspective, we hypothesize a positive impact of perceived innovativeness on the campaign outcome. Our database covers 191 campaigns launched in France on different platforms, drawing on over 2,000 individual assessments of the perceived innovativeness of the start‐ups involved, carried out by 176 participants with diverse backgrounds. We find support for our hypothesis from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…Most start-ups are eligible for tax relief (64%), while 9% of start-ups have nonexecutive directors on their boards. Only 6% of start-ups had patents before the launch of the initial equity crowdfunding offering (similar statistics are reported in previous studies, e.g., Le Pendeven & Schwienbacher, 2021; Rossi et al, 2021). The start-ups are on average 2.96 years old (median = 2.00) and the average total assets is £143.81K (median = 9.43).…”
Section: Resultssupporting
confidence: 86%
“…Most start-ups are eligible for tax relief (64%), while 9% of start-ups have nonexecutive directors on their boards. Only 6% of start-ups had patents before the launch of the initial equity crowdfunding offering (similar statistics are reported in previous studies, e.g., Le Pendeven & Schwienbacher, 2021; Rossi et al, 2021). The start-ups are on average 2.96 years old (median = 2.00) and the average total assets is £143.81K (median = 9.43).…”
Section: Resultssupporting
confidence: 86%
“…This idea is corroborated by Löfsten (2014) in his study of Swedish medium-sized technology-based industrial firms with R&D. Löfsten (2014) theorised and found empirical support for the positive causal relationship between innovation and financial performance. Similarly, in Le Pendeven and Schwienbacher's (2021) study of four large equity crowdfunding platforms, it was observed that more innovative business projects have a greater capacity to attract investors and achieve success. Thus, devoting significant attention to achieving great innovation can constitute a triggering mechanism for reaching firms' financial objectives.…”
Section: Literature Review and Hypothesesmentioning
confidence: 93%
“…From a broader perspective, it has pushed the boundaries of innovation in newly established and emerging projects. Large numbers of participants, from idea providers to users, customers, investors, and even brand or campaign sponsors, create unwanted effects on market structure and, willingly or unwillingly, create new challenges and opportunities for innovation management (Le Pendeven, and Schwienbacher, 2021).…”
Section: Practical Implicationsmentioning
confidence: 99%